Left atrial appendage closure in patients with chronic kidney disease: results from the German multicentre LAARGE registry - Fastner, Christian; Brachmann, Johannes; Lewalter, Thorsten; Zeymer, Uwe; Sievert, Horst; Borggrefe, Martin; Nienaber, Christoph; Weiß, Christian; Pleger, Sven Torsten; Ince, Hüseyin; Maier, Jens; Achenbach, Stephan; et al. (Clinical research in cardiology, 2021)
Chronic kidney disease (CKD) is associated with an increased complication rate after cardiac interventions. Although CKD has a high prevalence among atrial fibrillation patients, the impact of CKD on periprocedural complications and the outcome after an interventional left atrial appendage closure (LAAC) is unclear. The present study, therefore, aimed to investigate whether CKD influences the procedure’s effectiveness and safety.